Magnetismo a temperatura ambiente em polímeros derivados de politiofeno sintetizados eletroquimicamente - Forner, Alessandra Alves Correa (Universidade Federal de São Carlos, 2003)
In this thesis two polymers obtained from alkyl derivatives of thiophene, poly(3-methylthiophene) and poly(3-hexylthiophene) were studied. The effects of preparation variables on their electrochemical properties using the factorial design were analyzed. The preparation variables investigated were the supporting electrolyte and the synthesis applied potential. Then, a factorial design 22 was performed for each polymer and was made too a third factorial design 22, comparing the monomer and the potential. All the electrochemical analyses were made to understand the polymer behavior as a first step for the magnetic study. The magnetic properties of poly(3-methylthiophene) were analyzed and the weak ferromagnetic phase was observed in their pressed pellets as the polymer was partially doped with ClO4 - anions. This magnetic behavior was observed in full range from 1.8 K to 300 K with measurements performed using a SQUID magnetometer. The magnetization depends on the pressure used to prepare the pellets and the water content of the solvent used for the synthesis. The intrinsic character of this behavior was shown from atomic absorption analysis that discarded contamination. It was observed that the polymer shows different magnetic phases: diamagnetic, paramagnetic, ferromagnetic, antiferromagnetic and metamagnetic.
Keywords: Eletroquímica; Politiofenos; Magnetismo; Polímeros condutores; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA::ELETROQUIMICA